2014
DOI: 10.1021/jp502207n
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory versus Complete Active Space Self-Consistent Field Investigation of the Half-Metallic Character of Graphite-Like and Amorphous Carbon Nanoparticles

Abstract: Model carbon nanoparticles representative of the graphite-like and amorphous domains of active carbon are investigated with density functional theory (DFT) and complete active space self-consistent field (CASSCF) methods. Cyclic carbon clusters containing conjugated carbene groups are found to undergo Jahn-Teller distortion. More importantly, the half-metallicity, that is, the equal or similar stability of various spin states, previously suggested by DFT calculations for both types of nanosized clusters is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
(40 reference statements)
2
7
0
Order By: Relevance
“…3 Two independent theoretical studies have shown that amorphous carbon nanoparticles with low or no hydrogen-content might even be (semi-)metallic. 14,15 In stark contrast, we consider hydrogen passivated structures that feature large band gaps because these are better models for the real situation, in which nonfunctionalized carbon surfaces and edges are unlikely.…”
Section: Introductionmentioning
confidence: 99%
“…3 Two independent theoretical studies have shown that amorphous carbon nanoparticles with low or no hydrogen-content might even be (semi-)metallic. 14,15 In stark contrast, we consider hydrogen passivated structures that feature large band gaps because these are better models for the real situation, in which nonfunctionalized carbon surfaces and edges are unlikely.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the C4Q2 cluster are analogous to that of the G‐4H bare‐edge cluster described in Ref. . The cluster is paramagnetic and half‐metallic with pseudo‐degenerate spin states, that is, the singlet and triplet states are almost equal in energy.…”
Section: Resultsmentioning
confidence: 60%
“…An analogous situation was reported previously for polyconjugated carbon materials. 44 Some prompts for appropriate selection can be derived from analysis of the electronic structure of the neutral forms of the complexes. The ''additional'' electron should occupy a spin-up LUMO or spin-down LUMO of the species, so comparison of their energies (Table 4) can indicate the preferable multiplicity of the reduced state.…”
Section: Modeling Of Complex Reductionmentioning
confidence: 99%